The Credit Capacity Of Iraqi Private Banks With The Possibility Of Developing Them - Khitam Hatim Hamuwd; Aqeel Alwan Mohsen (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The credit capacity has a distinguished role in the development of banking work, as it contributes to achieving many goals in the economies of countries and increasing production. The credit capacity of Iraqi private banks, and the research concluded that the indicators of credit capacity are high in some private banks and low in others, which requires the need to present modern models to develop the credit capacity of Iraqi private banks.